EXPERIMENTAL AND MORPHOLOGICAL SUBSTANTIATION OF TUBULAR BIOLOGICAL STRUCTURES OBLITERATION BY MEANS OF HIGH-FREQUENCY ELECTRIC WELDING OF TISSUES - Kobzar, O.B.; Doroshenko, S.V.; Parkhomenko, M.V.; Khvorostyana, T.T.; Prymachenko, V.I. (World of Medicine and Biology, 2020)
We investigated the effect of high-frequency electric current on the simulated fistula of the digestive canal. We have identified the optimal parameters of the generator necessary for the destruction of the mucous membrane. Morphological methods confirmed the effectiveness of the current in destroying the tunica serosa of the fistula.
Keywords: electric welding of biological tissues; morphological changes; intestinal fistula